2010
DOI: 10.1111/j.1442-9071.2010.02198.x
|View full text |Cite
|
Sign up to set email alerts
|

Laser epithelial keratomileusis in 2010 – a review

Abstract: Photorefractive keratectomy, laser epithelial keratomileusis (LASEK) and Epi-LASIK are all variants of a similar type refractive surgery involving laser on the surface of the cornea and differ mainly in management of the epithelium. Although laser in situ keratomileusis (LASIK) is currently the most popular form of refractive surgery, LASEK is the procedure of choice in some patients. We highlight potential complications of LASEK and how these may be managed. Following laser refractive surgery, corneal thickne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
57
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(57 citation statements)
references
References 56 publications
(51 reference statements)
0
57
0
Order By: Relevance
“…Therefore, it can not only decrease the flap-related complications in LASIK but also reduce the delayed visual recovery, postoperative pain, and subepithelial haze in photorefractive keratectomy. [2][3][4] However, several complications related with LASEK procedures still exist, such as dry eye, corneal haze, delayed epithelial healing, ectasia, and infection. 4 Among these, dry eye is a disorder of the tear film caused by tear deficiency or excessive tear evaporation, which commonly occurs after LASEK and may negatively influence patients' satisfaction with the outcome of the procedure.…”
mentioning
confidence: 99%
“…Therefore, it can not only decrease the flap-related complications in LASIK but also reduce the delayed visual recovery, postoperative pain, and subepithelial haze in photorefractive keratectomy. [2][3][4] However, several complications related with LASEK procedures still exist, such as dry eye, corneal haze, delayed epithelial healing, ectasia, and infection. 4 Among these, dry eye is a disorder of the tear film caused by tear deficiency or excessive tear evaporation, which commonly occurs after LASEK and may negatively influence patients' satisfaction with the outcome of the procedure.…”
mentioning
confidence: 99%
“…However, exceptions were recently reported with thin-flap LASIK. 16,17 Laser-assisted subepithelial keratomileusis [18][19][20][21][22][23][24][25][26][27] is a surface ablation procedure that combines certain elements of LASIK and PRK. Manual epithelial debridement produces scratches and nicking in Bowman layer and leaves variable amounts of epithelium 28,29 ; therefore, dilute alcohol is used in LASEK to loosen the epithelial adhesion to the corneal stroma.…”
mentioning
confidence: 99%
“…LASEK is more comfortable and less traumatic for patients with deep set eyes or narrow palpebral apertures, where the application of a laser keratome may be more difficult. Recent results have shown that LASEK is an effective option, a safe and successful procedure; however, the LASEK procedure involves chemically reducing the corneal epithelium adhesion to the underlying Bowman's layer using a diluted solution of alcohol, which is potentially toxic to the epithelium and corneal stroma (1). Although after treatment with alcohol, the cornea is washed using cold-balanced salt solution, the toxic effects of alcohol on the cornea cannot be neglected.…”
Section: Introductionmentioning
confidence: 99%
“…Since Jose Barraquer recognized this fact and was the first to introduce lamellar refractive surgery techniques, many techniques have been developed, such as photorefractive keratectomy (PRK), laser in situ keratomileusis (LASIK) and laser epithelial keratomileusis (LASEK), all of which involve the removal of corneal tissue (1). LASEK was performed by Azar et al in 1996, which they termed alcohol-assisted flap PRK (2).…”
Section: Introductionmentioning
confidence: 99%